Socio-economic transformation of original communities following the conversion of agricultural land to the new town of Bandar Baru Bumi Serpong Damai, Tangerang, Banten, Indonesia - Ratnawati Yuni Suryandari, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2008)
In conclusion, the conversion of agricultural land into urban uses in the study area had not enhanced the Recently, cities in Java were experiencing the process of internal reconstruction both socio-economically and physically whereby at the urban fringes, the agricultural land was converted into new towns and industrial centres. The objective of this paper is to describe the socio-economic consequences of the original populace who were directly affected by the conversion of their agricultural land into the Bumi Serpong Damai (BSD) New Town, Tangerang, Banten, Indonesia based on the findings of a field study conducted in 2004-2005 involving 256 heads of households who remained residing in their original villages and 61 heads of households who had migrated from their native villages. The study found that overall, the scores for improved and favourable socio-economic consequences (42.6%) were lower than those of the deteriorating and unfavourable consequences (57.4%) for both original villagers who stayed and those who had migrated.quality of life and living standards of most of the original populace of that area. By implication, the biggest benefit of the conversion of the original agricultural land-use into the capitalist city development went to the capitalist investors and the new middle class entrants. In contrast, this development had largely disenfranchised the original inhabitants who were little more than simple proletariats and small producers.As such, the BSD New Town is not an ideal nor appropriate development model for Indonesia as it has proved to be least local friendly